Гетьман Данило Апостол та наступ російського царату на українську автономію. (Zaporizhzhia Historical Review, 2021)
Research the methods and peculiarities of Russian advance on the Ukrainian autonomy during the management of D. Apostola. The question is about defending the national ideas from the political point of view D. Apostol.